Corrigendum to “Recovery of valuable metals from cathodic active material of spent lithium-ion batteries: Leaching and kinetic aspects” [Waste Manage. 45 (2015) 306–313, (S0956053X15003815), (10.1016/j.wasman.2015.05.027)] - Meshram P.; Pandey B.D.; Mankhand T.R. (My University, 2025)
The authors regret, 50 g/L is written as 50% PD at seven instances in the published paper. The whole paper deals with using 50 g/L pulp density as the optimal solid: liquid ratio and concludes the same. The revised phrases are as follows: • 50% PD in the caption of Table 2 should be read as 50 g/L. [Table 2: XRD phase analysis of cathode powder and the leach residues at different time intervals (Conditions: 1 M H2SO4, 368 K and 50 g/L PD)].• 50% PD in the caption of Fig. 6 should be read as 50 g/L. [Fig. 6: Effect of temperature on the leaching of cathode active material using 1 M H2SO4 at 50 g/L PD in 240 min].• 50% PD in the section 3.4 should be read as 50 g/L. Characterization of the leach residue: Upon leaching with 1 M H2SO4 at 368 K and 50 g/L PD in 60 min the major phases were identified to be…….• 50% PD in the caption of Fig. 12 should be read as 50 g/L. [Fig. 12: SEM-EDAX analysis of residue in 60 min leaching with 1 M H2SO4 at 368 K and 50 g/L PD].• 50% PD in the caption of Fig. 13 should be read as 50 g/L. [Fig. 13: SEM-EDAX analysis of residue in 120 min leaching with 1 MH2SO4 at 368 K and 50 g/L PD].• 50% PD in the caption of Fig. 14 should be read as 50 g/L. [Fig. 14: SEM-EDAX analysis of residue in 240 min leaching with 1 M H2SO4 at 368 K and 50 g/L PD].• 50% PD in the caption of Table 3 should be read as 50 g/L. [Table 3: SEM-EDS analyses of leach residues with time at 1 M H2SO4, 368 K, and 50 g/L PD].The authors would like to apologise for any inconvenience caused. © 2022 Elsevier Ltd